IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL TO IMPROVE STUDENTS' LEARNING INTEREST - Dila Hana Isromi; Darwanto Darwanto (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2025)
his research was conducted at MTs Negeri 2 North Lampung in class VIII 2. which was conducted on July 21, 2025-July 31, 2025. The type of research used was Classroom Action Research (CAR) which was conducted in 2 cycles, each cycle consisting of 4 stages: (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. Data collection can be done through three steps, namely data reduction, data presentation, and drawing conclusions. The results of the study showed that the classical completeness of students' interests in Cycle I reached 82%, increasing by 7% in Cycle II to 89%. Student learning outcomes in the cognitive domain of Cycle I classical completeness reached 73%, increasing by 1% in Cycle II to 74%. Thus, it can be concluded that the application of the Discovery Learning learning model can increase the learning interest of class VIII 2 students at MTs Negeri 2 North Lampung.